Wie schreibt man das??! - Nur Ilyana, Mohd Ariff; Siew Ling, Koo; Yanti Salina, Shaari
Deutsch, the main language that is widely used in Germany. Besides that, it is also the main language for various countries such as Belgium, Austria and Switzerland. Even though German alphabets look similar to English but their pronunciations are totally different. Once, we were introduced to the phrase “Wie schreibt man das?”, we repeatedly practiced it using the appropriate German spelling in the classroom.